Stock Repurchases and Executive Compensation Contract Design: The Role of Earnings per Share Performance Conditions - Young, Steven; Yang, Jing (The Accounting Review, 2011)
ABSTRACT: We examine the link between firms’ stock repurchase activity and the presence of earnings per share (EPS) performance conditions in executive compensation contracts. Findings reveal a strong positive association between repurchases and EPS-contingent compensation arrangements. Further analysis suggests net benefits to shareholders from this association. Specifically, repurchasers experience larger increases in total payouts; the positive association between repurchases and cash performance is more pronounced for firms with EPS targets in the presence of surplus cash; undervalued firms with EPS targets are more likely to signal mispricing through a repurchase; and repurchasers with EPS conditions are associated with lower abnormal accruals. We find no evidence that EPS-driven repurchases impose costs on shareholders in the form of investment myopia.